Writing academically: Experiences of Indonesian graduate students studying abroad - Fhonna, Rahmi; Ismail, Fitriah (Accentia: Journal of English Language and Education, 2022)
It requires particular approaches to produce a qualified academic writing since it is a basis of understanding, representing the quality of the writers thinking and potential ideas. This study was conducted to investigate the experiences of two Indonesian students taking a Masters degree at the University of Adelaide, in constructing academic writing. Interview, to give an ethnographic perspective, was used in this study and the participants were asked with seven open-ended questions. The findings showed that, the students identified second language difficulties with regard to writing in general (grammatical and orthographic category), and difficulties with understanding the readings, and translating that into critical analysis to support argumentation. English as a foreign language (EFL) educational background was another issue to appear during the interview in relation to their obscurities in constructing the writing academically. Peer review, furthermore, also played a significant role to help them produce a better writing through proofreading.